Thrombolytic activity and antibacterial activity optimize staphylokinase enzyme production from Staphylococcus aureus - Bilal Husam Jasim; Rand Jabbar Sattar; Maryam Dhary Kamel; Entesar Hussein Ali; Majid Sakhi Jabir; Maryam Hussein Saddi; Bassam Shaker Mahmood; Zahraa Abbas Fadhil (Universitas Gadjah Mada, 2025)
Staphylokinase is a virulence factor produced by Staphylococcus aureus that enhances its ability to degrade proteins, contributing to tissue damage and increased bacterial invasiveness. This investigation studied staphylokinase production by S. aureus isolates obtained from wound and burn patients. Optimal conditions for enhancing staphylokinase production in Sato’s component were determined. These conditions included a carbon source (glucose), a nitrogen source (yeast extract), an inoculum size of 1%, an incubation temperature of 37 °C, and a pH of 7. Optimization of the medium components resulted in a significant increase in staphylokinase production (26.4 U/mL), representing a 2.23‐fold rise compared to production in the unoptimized Sato’s component. The crude staphylokinase enzyme exhibited thrombolytic activity against human blood clots, achieving 42% clot lysis. However, the crude enzyme showed no antibacterial activity against the tested bacteria (Streptomyces and Escherichia coli). This study represents the first report of optimized media for enhancing staphylokinase production from S. aureus. The research is significant because it establishes a method for improving the production of highly active staphylokinase from S. aureus, which has potential applications as a thrombolytic agent.